Aetiology of non-malaria acute febrile illness fever in children in rural Guinea-Bissau: a prospective cross-sectional investigation - Gutierrez, Rui; Landa, Mariana; Sambou, Masse; Bassane, Hubert; Dia, Ndongo; Djalo, Alfa Saliu; Domenichini, Chiara; Fall, Gamou; Faye, Martin; Faye, Ousmane; Fernandez-Garcia, Maria-Dolores; Flevaud, Laurence; et al. (Frontiers in Epidemiology, 2024)
Background: With growing use of parasitological tests to detect malaria and decreasing incidence of the disease in Africa; it becomes necessary to increase the understanding of causes of non-malaria acute febrile illness (NMAFI) towards providing appropriate case management. This research investigates causes of NMAFI in pediatric out-patients in rural Guinea-Bissau.Methods: Children 0-5 years presenting acute fever (≥38º) or history of fever, negative malaria rapid diagnostic test (mRDT) and no signs of specific disease were recruited at the out-patient clinic of 3 health facilities in Bafatá province during 54 consecutive weeks (dry and rainy season). Medical history was recorded and blood, nasopharyngeal, stool and urine samples were collected and tested for the presence of 38 different potential aetiological causes of fever.Results: Samples from 741 children were analysed, the protocol was successful in determining a probable aetiological cause of acute fever in 544 (73.61%) cases. Respiratory viruses were the most frequently identified pathogens, present in the nasopharynx samples of 435 (58.86%) cases, followed by bacteria detected in 167 (22.60%) samples. Despite presenting negative mRDTs, P. falciparum was identified in samples of 24 (3.25%) patients.This research provides a description of the aetiological causes of NMAFI in West African context. Evidence of viral infections were more commonly found than bacteria or parasites.